Renewable adsorbent for removing heavy metal ions and preparation method thereof

Through the chemical modification of the modified loofah and the combination of salicylate aminothiourea triazine, an efficient heavy metal ion adsorbent is formed, which solves the shortcomings of the existing adsorbents in terms of adsorption performance and regeneration capabilities, and achieves efficient heavy metal ion removal and good regeneration performance.

CN119869469AActive Publication Date: 2025-04-25GUANGDONG YICHENG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510381613.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The existing heavy metal ion adsorbents have shortcomings in adsorption performance and regeneration capabilities, resulting in high costs, large energy consumption or secondary pollution, and the preparation process of nanomaterials is complex, environmental risks and difficult to recover.

Method used

Modified loofah is used as the base material, and epoxy and thiopropionate functional groups are grafted on its surface by chemical modification, combined with salicyaldehyde aminothiourea triazine, forming covalent bonds and sulfide bond connections, enhancing adsorption performance and regeneration efficiency.

Benefits of technology

The saturation adsorption capacity and regeneration efficiency of heavy metal ion adsorbents are significantly improved, and the removal rate of Pb²⁺ can still be maintained above 85% after 5 adsorption-desorption cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869469A_ABST
    Figure CN119869469A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heavy metal adsorbents, in particular to a reproducible adsorbent for removing heavy metal ions and a preparation method of the reproducible adsorbent. The renewable adsorbent is prepared from the following raw materials in parts by weight: 10 to 15 parts of modified loofah sponge and 8 to 12 parts of salicylaldehyde thiosemicarbazide triazine; the modified loofah sponge is prepared from the following preparation raw materials: loofah sponge, epoxy chloropropane and tetrakis (3-mercaptopropionic acid) pentaerythritol ester, and the salicylaldehyde thiosemicarbazide triazine is prepared from the following components in parts by weight: 2 to 3 parts of 5-chloromethyl salicylaldehyde, 1.2 to 1.6 parts of thiosemicarbazide and 6.5 to 9.7 parts of cyanuric chloride. The renewable adsorbent prepared by the invention has relatively high adsorption capacity and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy metal adsorbents, and in particular to a regenerable adsorbent for removing heavy metal ions and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization, heavy metal ions enter the environment through different pathways and continue to accumulate, and heavy metal pollution has become one of the main pollutants in water pollution. The wastewater discharged by industries such as electroplating, mining, metallurgy and chemical industry contains toxic heavy metal ions such as lead (Pb²⁺), cadmium (Cd²⁺), mercury (Hg²⁺), arsenic (As³⁺), etc., which pose a serious threat to the ecological environment and human health due to their non-degradability and bioaccumulation. Although traditional water treatment technologies such as chemical precipitation, membrane separation and electrolysis have certain effects, they generally have problems such as high cost, high energy consumption or secondary pollution. Among them, the adsorption method is widely used because of its simple operation and controllable cost, but its core bottleneck lies in the performance and regeneration ability of the adsorbent. Currently, commonly used adsorbents include activated carbon, zeolite, ion exchange resin and biomass materials. Although activated carbon has a high adsorption capacity, regeneration requires high-temperature calcination or strong acid treatment, which leads to structural collapse and performance degradation; synthetic resins are expensive and have low regeneration efficiency; and although natural clay or agricultural waste (such as rice husks and straw) are widely available, the unmodified raw materials have poor adsorption selectivity and low mechanical strength, making them difficult to recycle. In recent years, although nanomaterials (such as graphene and metal-organic frameworks) have shown high adsorption efficiency, their complex preparation process, environmental risks and recycling difficulties have limited their large-scale application. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a regenerable adsorbent for removing heavy metal ions and a preparation method thereof.

[0004] The present invention is achieved through the following technical solutions: A regenerable adsorbent for removing heavy metal ions comprises the following raw materials in parts by weight: 10-15 parts of modified loofah sponges and 8-12 parts of salicylaldehyde thiosemicarbazide triazine.

[0005] Furthermore, the preparation method of the modified loofah comprises the following steps: A1: Cut the loofah into pieces of 2×2 cm in size, soak them in clean water, change the water every 2 h, and wash them repeatedly. After 24 h, immerse them in 5% (w / v) NaOH solution, stir them continuously at 60°C and 200-300 rpm for 3 h, wash them with ultrapure water until they are neutral, and dry them in a vacuum at 80°C to obtain pretreated loofah. A2: Add the pretreated loofah obtained in step A1 to a 3 mol / L NaOH solution, add epichlorohydrin and anhydrous ethanol, place in a 50°C constant temperature water bath, stir and react for 3 h, wash with ethanol, and dry to obtain epoxidized loofah; A3:N 2 Under protection, the epoxidized loofah obtained in step A2 and pentaerythritol tetrakis (3-mercaptopropionic acid) ester are added to ethanol, ultrasonically dispersed at 300-400 W for 20-30 min, triethylamine is added, and the reaction is stirred at room temperature for 3-4 h, washed with anhydrous ethanol, and vacuum dried to obtain a modified loofah.

[0006] Furthermore, in step A2, the usage ratio of the pretreated loofah, NaOH solution, epichlorohydrin and anhydrous ethanol is 1 g:50 mL:15 mL:10 mL.

[0007] Furthermore, in step A3, the usage ratio of the epoxidized loofah, pentaerythritol tetrakis(3-mercaptopropionic acid), ethanol and triethylamine is 1 g:2 g:40-60 mL:6-10 mL.

[0008] Furthermore, the raw materials for preparing the salicylaldehyde thiosemicarbazide triazine include the following components in parts by weight: 6-9 parts of 5-chloromethyl salicylaldehyde, 4-6 parts of thiosemicarbazide, and 2-3 parts of cyanuric chloride.

[0009] Furthermore, the preparation method of salicylaldehyde thiosemicarbazide triazine comprises the following steps: B1: Add the ethanol solution of 5-chloromethyl salicylaldehyde dropwise to the ethanol solution of thiosemicarbazide, heat and reflux for 4-5 hours, cool to room temperature, filter, wash the filter cake with ethanol, and dry in vacuo at 60-70°C to obtain chloromethyl salicylaldehyde thiosemicarbazide; B2: Add cyanuric chloride to 1,4-dioxane and mix well to obtain a mixed solution; add chloromethyl salicylaldehyde thiosemicarbazone and potassium carbonate obtained in step B1 to 1,4-dioxane and mix well; add the mixed solution dropwise in an ice water bath, stir well, heat to 80-90°C, and react for 8-12 h; B3: After the reaction in step B2 is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water and dried under vacuum at 60-70°C to obtain salicylaldehyde aminothiourea triazine.

[0010] Furthermore, in step B1, the mass concentration of 5-chloromethyl salicylaldehyde in ethanol in the ethanol solution of 5-chloromethyl salicylaldehyde is 40-50 mg / mL.

[0011] Furthermore, in step B1, the mass concentration of thiosemicarbazide in ethanol in the ethanol solution of thiosemicarbazide is 20-25 mg / mL.

[0012] Furthermore, in step B2, the mass concentration of cyanuric chloride in 1,4-dioxane is 20-40 mg / mL.

[0013] Furthermore, in step B2, the mass concentration of the chloromethyl salicylaldehyde thiosemicarbazone in 1,4-dioxane is 10-15 mg / mL.

[0014] Furthermore, in step B2, the mass ratio of the chloromethyl salicylaldehyde thiosemicarbazone to potassium carbonate is 1:3.

[0015] Furthermore, the present invention also provides a method for preparing the regenerable adsorbent for heavy metal ion removal, comprising the following steps: S1: Under nitrogen protection, take modified loofah, K 2 CO 3 and salicylaldehyde thiosemicarbazide triazine were added to ethyl acetate and reacted at 80 °C for 24 h; S2: After the reaction in step S1 is completed, the mixture is cooled to room temperature and filtered, the filter cake is washed with deionized water and anhydrous ethanol, and vacuum dried to obtain a regenerable adsorbent for heavy metal ion removal.

[0016] Furthermore, in step S1, the salicylaldehyde thiosemicarbazide triazine, K 2 CO 3 The dosage ratio of ethyl acetate is 1 g:2 g:20 mL.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a regenerable adsorbent for heavy metal ion removal and a preparation method thereof. The loofah sponge is used as a base material, its natural three-dimensional porous structure is fully utilized, and the heavy metal ion adsorption performance and regeneration efficiency are significantly improved through chemical modification. The invention uses epichlorohydrin to graft epoxy groups on the surface of the loofah sponge, introduces active epoxy groups on the surface of the loofah sponge through epoxidation treatment, provides uniform anchoring points for subsequent thiolization, avoids uneven distribution of functional groups, and selectively reacts with pentaerythritol tetrakis(3-mercaptopropionic acid) to form a stable thioether bond connection and a covalent bond connection. The grafted layer is not easy to fall off under acidic elution conditions, provides abundant thiol groups (-SH), and forms stable coordination bonds with heavy metal ions through soft acid-soft base. The invention causes 5-chloromethyl salicylaldehyde to undergo a condensation reaction with semicarbazide, reacts the aldehyde group of the 5-chloromethyl salicylaldehyde with the amino group of the semicarbazide to form a Schiff base bond, obtains an intermediate chloromethyl salicylaldehyde thiosemicarbazide containing a chloromethyl group and a Schiff base bond, and the amino group of the intermediate undergoes a nucleophilic substitution reaction with cyanuric chloride to obtain the -NH 2Attack a chlorine atom of cyanuric chloride to generate a substitution product, and retain the active chlorine atom for subsequent functionalized grafting. The prepared salicylaldehyde aminothiourea triazine contains a triazine ring, a Schiff base bond and an aminothiourea group, and its nitrogen, sulfur and other atoms can chelate or ion exchange with metal ions, and the retained active chlorine atom provides a reaction site for subsequent bonding with the thiol group of the modified loofah; at the same time, the hydroxyl group of the natural cellulose skeleton of the loofah further enhances the capture ability of heavy metals through electrostatic adsorption. The synergistic effect of the above functional groups significantly improves the saturated adsorption capacity of the adsorbent for heavy metal ions. The salicylaldehyde aminothiourea triazine of the present invention forms a covalent bridge with the thiol group of the modified loofah through a nucleophilic substitution reaction, and the salicylaldehyde aminothiourea triazine is combined with the thiol group on the surface of the modified loofah, and chemical bonding gives the adsorbent structural stability. The acidic eluent can protonate the thiol group, weaken the coordination effect with the metal, and competitively replace the metal ions bound by the Schiff base bond. Experiments show that after 5 adsorption-desorption cycles, the removal rate of Pb²⁺ by the adsorbent is still >85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a scanning electron microscope image of the adsorbent described in Example 1 of the present invention; Figure 2 is the chemical structural formula of salicylaldehyde thiosemicarbazide triazine described in Example 1 of the present invention; Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of salicylaldehyde thiosemicarbazide triazine described in Example 1 of the present invention; Figure 4 The desorption effect of the adsorbents described in Examples 1-3 and Comparative Examples 1-2 of the present invention; Figure 5 The cycle performance of the adsorbent described in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention are purchased through commercial channels.

[0021] Example 1: A regenerable adsorbent for removing heavy metal ions, comprising the following raw materials in parts by weight: 15 parts of modified loofah and 12 parts of salicylaldehyde thiosemicarbazide triazine.

[0022] The preparation method of the modified loofah comprises the following steps: A1: Cut the loofah into pieces of 2×2 cm in size, soak them in clean water, change the water every 2 h, and wash them repeatedly. After 24 h, immerse them in 5% (w / v) NaOH solution, stir them continuously at 60°C and 300 rpm for 3 h, wash them with ultrapure water until they are neutral, and dry them in a vacuum at 80°C to obtain pretreated loofah. A2: Add 50 g of the pretreated loofah obtained in step A1 into 2500 mL of 3 mol / L NaOH solution, add 750 mL of epichlorohydrin and 500 mL of anhydrous ethanol, place in a 50°C constant temperature water bath, stir and react for 3 h, wash with ethanol, and dry to obtain epoxidized loofah; A3:N 2 Under protection, 50 g of the epoxidized loofah obtained in step A2 and 100 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester were added to 3000 mL of ethanol, ultrasonically dispersed at 400 W for 30 min, 500 mL of triethylamine was added, and the reaction was stirred at room temperature for 4 h. The mixture was washed with anhydrous ethanol and dried in vacuo to obtain a modified loofah.

[0023] The raw materials for preparing salicylaldehyde thiosemicarbazide triazine include the following components in parts by weight: 9 parts of 5-chloromethyl salicylaldehyde, 6 parts of thiosemicarbazide and 3 parts of cyanuric chloride.

[0024] The preparation method of salicylaldehyde thiosemicarbazide triazine comprises the following steps: B1: Prepare 5-chloromethyl salicylaldehyde in an ethanol solution at a ratio of 50 mg / mL with 9 g of 5-chloromethyl salicylaldehyde, add dropwise to 6 g of thiosemicarbazide in an ethanol solution at a ratio of 25 mg / mL, heat and reflux for 5 h, cool to room temperature, filter, wash the filter cake with ethanol, and vacuum dry at 70°C to obtain chloromethyl salicylaldehyde thiosemicarbazide; B2: Add 3 g of cyanuric chloride to 75 mL of 1,4-dioxane and mix well to obtain a mixed solution. Add the chloromethyl salicylaldehyde thiosemicarbazone obtained in step B1 and potassium carbonate to 1,4-dioxane and mix well. The mass ratio of chloromethyl salicylaldehyde thiosemicarbazone to potassium carbonate is 1:3, and the mass concentration of chloromethyl salicylaldehyde thiosemicarbazone in 1,4-dioxane is 15 mg / mL. Add the mixed solution dropwise in an ice-water bath, stir well, heat to 90°C, and react for 12 h. B3: After the reaction in step B2 is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water and dried under vacuum at 70° C. to obtain salicylaldehyde aminothiourea triazine.

[0025] This embodiment also provides a method for preparing the regenerable adsorbent for heavy metal ion removal, comprising the following steps: S1: Under nitrogen protection, take 15 g of modified loofah, K 2 CO 3 24 g of thiocarbamide and 12 g of salicylaldehyde were added to 240 mL of ethyl acetate and reacted at 80 °C for 24 h; S2: After the reaction in step S1 is completed, the mixture is cooled to room temperature and filtered, the filter cake is washed with deionized water and anhydrous ethanol, and vacuum dried to obtain a regenerable adsorbent for heavy metal ion removal.

[0026] Example 2: A regenerable adsorbent for removing heavy metal ions, comprising the following raw materials in parts by weight: 10 parts of modified loofah and 8 parts of salicylaldehyde thiosemicarbazide triazine.

[0027] The preparation method of the modified loofah comprises the following steps: A1: Cut the loofah into pieces of 2×2 cm in size, soak them in clean water, change the water every 2 h, and wash them repeatedly. After 24 h, immerse them in 5% (w / v) NaOH solution, stir them continuously at 60°C and 200 rpm for 3 h, wash them with ultrapure water until they are neutral, and dry them in a vacuum at 80°C to obtain pretreated loofah. A2: Add 20 g of the pretreated loofah obtained in step A1 to 1000 mL of 3 mol / L NaOH solution, add 300 mL of epichlorohydrin and 200 mL of anhydrous ethanol, place in a 50°C constant temperature water bath, stir and react for 3 h, wash with ethanol, and dry to obtain epoxidized loofah; A3:N 2 Under protection, 20 g of the epoxidized loofah obtained in step A2 and 40 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester were added to 800 mL of ethanol, ultrasonically dispersed at 300 W for 20 min, 120 mL of triethylamine was added, and the reaction was stirred at room temperature for 3 h, washed with anhydrous ethanol, and vacuum dried to obtain a modified loofah.

[0028] The raw materials for preparing salicylaldehyde thiosemicarbazide triazine include the following components in parts by weight: 6 parts of 5-chloromethyl salicylaldehyde, 4 parts of thiosemicarbazide and 2 parts of cyanuric chloride.

[0029] The preparation method of salicylaldehyde thiosemicarbazide triazine comprises the following steps: B1: Prepare 6 g of 5-chloromethyl salicylaldehyde in an ethanol solution at a ratio of 40 mg / mL, add dropwise to 4 g of thiosemicarbazide in an ethanol solution at a ratio of 20 mg / mL, heat and reflux for 4 h, cool to room temperature, filter, wash the filter cake with ethanol, and vacuum dry at 60°C to obtain chloromethyl salicylaldehyde thiosemicarbazide; B2: Add 2 g of cyanuric chloride to 100 mL of 1,4-dioxane and mix well to obtain a mixed solution. Add the chloromethyl salicylaldehyde thiosemicarbazone obtained in step B1 and potassium carbonate to 1,4-dioxane and mix well. The mass ratio of chloromethyl salicylaldehyde thiosemicarbazone to potassium carbonate is 1:3, and the mass concentration of chloromethyl salicylaldehyde thiosemicarbazone in 1,4-dioxane is 10 mg / mL. Add the mixed solution dropwise in an ice-water bath, stir well, heat to 80°C, and react for 8 h. B3: After the reaction in step B2 is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water and dried under vacuum at 60° C. to obtain salicylaldehyde aminothiourea triazine.

[0030] This embodiment also provides a method for preparing the regenerable adsorbent for heavy metal ion removal, comprising the following steps: S1: Under nitrogen protection, take 10 g of modified loofah, K 2 CO 3 16 g of chloranil and 8 g of salicylaldehyde thiosemicarbazide triazine were added into 160 mL of ethyl acetate and reacted at 80 °C for 24 h; S2: After the reaction in step S1 is completed, the mixture is cooled to room temperature and filtered, the filter cake is washed with deionized water and anhydrous ethanol, and vacuum dried to obtain a regenerable adsorbent for heavy metal ion removal.

[0031] Example 3: A regenerable adsorbent for removing heavy metal ions, comprising the following raw materials in parts by weight: 12 parts of modified loofah sponge and 10 parts of salicylaldehyde thiosemicarbazide triazine.

[0032] The preparation method of the modified loofah comprises the following steps: A1: Cut the loofah into pieces of 2×2 cm in size, soak them in clean water, change the water every 2 h, and wash them repeatedly. After 24 h, immerse them in 5% (w / v) NaOH solution, stir them continuously at 60°C and 250 rpm for 3 h, wash them with ultrapure water until they are neutral, and dry them in a vacuum at 80°C to obtain pretreated loofah. A2: Add 30 g of the pretreated loofah obtained in step A1 into 1500 mL of 3 mol / L NaOH solution, add 450 mL of epichlorohydrin and 300 mL of anhydrous ethanol, place in a 50°C constant temperature water bath, stir and react for 3 h, wash with ethanol, and dry to obtain epoxidized loofah; A3:N 2 Under protection, 30 g of the epoxidized loofah obtained in step A2 and 60 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester were added to 1500 mL of ethanol, ultrasonically dispersed at 350 W for 25 min, 240 mL of triethylamine was added, and the reaction was stirred at room temperature for 3.5 h. The mixture was washed with anhydrous ethanol and dried in vacuum to obtain a modified loofah.

[0033] The raw materials for preparing salicylaldehyde thiosemicarbazide triazine include the following components in parts by weight: 7.2 parts of 5-chloromethyl salicylaldehyde, 4.8 parts of thiosemicarbazide and 2.5 parts of cyanuric chloride.

[0034] The preparation method of salicylaldehyde thiosemicarbazide triazine comprises the following steps: B1: Add 7.2 g of 5-chloromethyl salicylaldehyde prepared at a ratio of 48 mg / mL of ethanol solution of 5-chloromethyl salicylaldehyde dropwise to 4.8 g of 24 mg / mL of ethanol solution of thiosemicarbazide prepared by heating under reflux for 4.5 h, cool to room temperature, filter, wash the filter cake with ethanol, and dry under vacuum at 65°C to obtain chloromethyl salicylaldehyde thiosemicarbazide; B2: Add 2.5 g of cyanuric chloride to 100 mL of 1,4-dioxane and mix well to obtain a mixed solution. Add the chloromethyl salicylaldehyde thiosemicarbazone obtained in step B1 and potassium carbonate to 1,4-dioxane and mix well. The mass ratio of chloromethyl salicylaldehyde thiosemicarbazone to potassium carbonate is 1:3, and the mass concentration of chloromethyl salicylaldehyde thiosemicarbazone in 1,4-dioxane is 12 mg / mL. Add the mixed solution dropwise in an ice-water bath, stir well, heat to 85°C, and react for 10 h. B3: After the reaction in step B2 is completed, the mixture is cooled to room temperature and filtered. The filter cake is washed with anhydrous ethanol and deionized water and dried under vacuum at 65° C. to obtain salicylaldehyde aminothiourea triazine.

[0035] This embodiment also provides a method for preparing the regenerable adsorbent for heavy metal ion removal, comprising the following steps: S1: Under nitrogen protection, take 12 g of modified loofah, K 2 CO 3 20 g of thiocarbamide and 10 g of salicylaldehyde were added to 200 mL of ethyl acetate and reacted at 80 °C for 24 h; S2: After the reaction in step S1 is completed, the mixture is cooled to room temperature and filtered, the filter cake is washed with deionized water and anhydrous ethanol, and vacuum dried to obtain a regenerable adsorbent for heavy metal ion removal.

[0036] The difference between Comparative Example 1 and Example 1 is that salicylaldehyde thiosemicarbazide triazine is not added, that is, the regenerable adsorbent is replaced by modified loofah.

[0037] The difference between Comparative Example 2 and Example 1 is that the regenerable adsorbent is replaced by pretreated loofah.

[0038] Experimental Example 1: The regenerable adsorbent prepared in Example 1 was observed using a scanning electron microscope. The scanning electron microscope image is as follows: Figure 1 shown. Figure 1The results show that the adsorbent of the present invention retains the natural three-dimensional porous skeleton structure of loofah, and the fiber surface is relatively rough with grooves, which is conducive to the adsorption of heavy metal pollutants.

[0039] Experimental Example 2: Salicylaldehyde thiosemicarbazide triazine was prepared according to the method of Example 1, and its chemical structure is as follows: Figure 2 As shown, Figure 2 The results showed that the aldehyde group of 5-chloromethyl salicylaldehyde reacted with the amine group of thiosemicarbazide to undergo a Schiff base reaction, and 5-chloromethyl salicylaldehyde and thiosemicarbazide were covalently bonded to obtain chloromethyl salicylaldehyde thiosemicarbazide. The obtained product contained an amino group, which reacted with the chlorine atom group of cyanuric chloride. The chloromethyl salicylaldehyde thiosemicarbazide replaced the chlorine atom in cyanuric chloride to obtain salicylaldehyde thiosemicarbazide triazine. The hydrogen nuclear magnetic resonance spectrum is shown in Figure 3 As shown, 1 H NMR (300 MHz, DMSO-d 6 ), chemical shift δ: 11.67 (3H), 11.55 (3H), 11.11 (3H), 8.74 (3H), 7.69 (3H), 7.22 (3H), 6.95 (3H), 4.64 (6H).

[0040] Experimental Example 3: Take 20 mL of simulated wastewater sample with an initial lead ion concentration of 200 mg / L, add 10 mg of the regenerable adsorbent of Example 1-3 and Comparative Example 1-2, and adsorb at 180 r / min at room temperature for 6 h. Take the supernatant to determine the lead ion concentration and calculate the adsorption capacity. The results are as follows: Figure 4 shown.

[0041] Figure 4 The results show that the adsorption capacity and adsorption rate of the adsorbents in Examples 1-3 for lead ions are significantly higher than those in Comparative Examples 1-2. Among them, Comparative Example 1 only uses modified loofah as an adsorbent without grafting salicylaldehyde aminothiourea triazine, and Comparative Example 2 uses pretreated loofah as an adsorbent. Both Comparative Examples 1-2 significantly reduce the groups that can coordinate with heavy metals, and the adsorption performance for heavy metal ions decreases.

[0042] Experimental Example 4: The adsorbent was dried after reaching saturation, a HAC solution with a concentration of 0.1 mol / L was prepared, 20 mg of the adsorbent was added to reach the saturated adsorption capacity, and the adsorbent was shaken at 180 r / min for 6 h at room temperature, rinsed with distilled water and dried, and desorbed. Five cycles of adsorption-desorption tests were performed, and the removal rate of lead ions was calculated after each adsorption of lead ions. The results are as follows: Figure 5 shown.

[0043] Figure 5The results show that the adsorbent prepared in Example 1 can maintain a removal rate of more than 85% for lead ions after 5 adsorption and desorption cycles. After the cycle of Comparative Example 1-2, the removal rate is significantly reduced compared with that of Example 1. Due to the lack of active sites in Comparative Example 1-2, the original sites are passivated after repeated use, and the cycle capacity decreases rapidly, and the cycle stability decreases.

[0044] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A regenerable adsorbent for heavy metal ion removal, characterized in that: The method comprises the following raw materials in parts by weight: 10-15 parts of modified loofah sponge and 8-12 parts of salicylaldehyde thiosemicarbazide triazine; The preparation method of the modified loofah comprises the following steps: A1: Soaking and scrubbing a loofah with clean water, immersing the loofah in a NaOH solution, stirring, washing, and drying to obtain a pretreated loofah; A2: Add the pretreated loofah obtained in step A1 to a NaOH solution, add epichlorohydrin and anhydrous ethanol, place in a constant temperature water bath, stir to react, wash, and dry to obtain an epoxidized loofah; A3: Under N2 protection, the epoxidized loofah obtained in step A2 and pentaerythritol tetrakis(3-mercaptopropionic acid) ester are added to ethanol, ultrasonicated, triethylamine is added, stirred for reaction, washed, and dried to obtain a modified loofah; The preparation method of salicylaldehyde thiosemicarbazide triazine comprises the following steps: B1: adding the ethanol solution of 5-chloromethyl salicylaldehyde dropwise to the ethanol solution of thiosemicarbazide, heating to reflux, cooling, suction filtering, washing, and drying to obtain chloromethyl salicylaldehyde thiosemicarbazide; B2: Add cyanuric chloride to 1,4-dioxane and mix well to obtain a mixed solution, add the chloromethyl salicylaldehyde thiosemicarbazone obtained in step B1 and potassium carbonate to 1,4-dioxane and mix well, add the mixed solution dropwise in an ice water bath, stir well, heat, and react; B3: After the reaction in step B2 is completed, the mixture is cooled to room temperature, filtered, the filter cake is washed, and dried to obtain salicylaldehyde thiosemicarbazide triazine.

2. The regenerable adsorbent for heavy metal ion removal according to claim 1, characterized in that: In step A2, the amount ratio of the pretreated loofah, NaOH solution, epichlorohydrin and anhydrous ethanol is 1 g: 50 mL: 15 mL: 10 mL; in step A3, the amount ratio of the epoxidized loofah, pentaerythritol tetrakis(3-mercaptopropionic acid), ethanol and triethylamine is 1 g: 2 g: 40-60 mL: 6-10 mL.

3. The regenerable adsorbent for heavy metal ion removal according to claim 1, characterized in that: In step B1, the mass concentration of 5-chloromethyl salicylaldehyde in ethanol is 40-50 mg / mL; the mass concentration of thiosemicarbazide in ethanol is 20-25 mg / mL.

4. The regenerable adsorbent for heavy metal ion removal according to claim 3, characterized in that: In step B2, the mass concentration of cyanuric chloride in 1,4-dioxane is 20-40 mg / mL; the mass concentration of chloromethyl salicylaldehyde thiosemicarbazone in 1,4-dioxane is 10-15 mg / mL; and the mass ratio of chloromethyl salicylaldehyde thiosemicarbazone to potassium carbonate is 1:

3.

5. A method for preparing a regenerable adsorbent for heavy metal ion removal according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Under nitrogen protection, take modified loofah, K2CO3 and salicylaldehyde aminothiourea triazine and add them to ethyl acetate for reaction; the dosage ratio of salicylaldehyde aminothiourea triazine, K2CO3 and ethyl acetate is 1 g:2 g:20 mL; S2: After the reaction in step S1 is completed, the mixture is cooled, filtered, washed and dried to obtain a regenerable adsorbent for removing heavy metal ions.

Citation Information

Patent Citations

  • Multifunctional chelating ion-exchange fibers, and preparation method and application thereof

    CN102430435A

  • Preparation and application of cysteine modified loofah adsorbent

    CN103447009A

  • Preparation method and applications of epichlorohydrin-modified vegetable sponge adsorbent

    CN103464116A

  • Coal gangue modified heavy metal adsorbent and preparation method thereof

    CN117696021A

  • Weather-resistant transparent adhesive, preparation method and application of weather-resistant transparent adhesive to adhesion of weather-resistant and wear-resistant transparent film and color-coated sheet

    CN119432279A